Loss to follow‐up: A significant barrier in the treatment cascade with direct‐acting therapies. Issue 3 (2nd December 2019) - Darvishian, Maryam; Wong, Stanley; Binka, Mawuena; Yu, Amanda; Ramji, Alnoor; Yoshida, Eric M.; Wong, Jason; Rossi, Carmine; Butt, Zahid A.; Bartlett, Sofia; Pearce, Margo E.; Samji, Hasina; et al.
Abstract: Effectiveness of direct‐acting antiviral (DAA) therapies could be influenced by patient characteristics such as comorbid conditions, which could lead to premature treatment discontinuation and/or irregular medical follow‐ups. Here, we evaluate loss to follow‐up and treatment effectiveness of sofosbuvir/ledipasvir ± ribavirin (SOF/LDV ± RBV), ombitasvir/paritaprevir/ritonavir + dasabuvir ± ribavirin (OBV/PTV/r + DSV ± RBV) for hepatitis C virus (HCV) genotype 1 (GT1) and sofosbuvir + ribavirin (SOF + RBV) for genotype 3 (GT3) in British Columbia Canada: The British Columbia Hepatitis Testers Cohort includes data on individuals tested for HCV since 1992, integrated with medical visit, hospitalization and prescription drug data. HCV‐positive individuals who initiated DAA regimens, irrespective of treatment completion, for GT1 and GT3 until 31 December, 2017 were included. Factors associated with sustained virological response (SVR) and loss to follow‐up were assessed by using multivariable logistic regression models. In total 4477 individuals initiated DAAs. The most common prescribed DAA was SOF/LDV ± RBV with SVR of 95%. The highest SVR of 99.5% was observed among OBV/PTV/r + DSV‐treated patients. Overall, 453 (10.1%) individuals were lost to follow‐up. Higher loss to follow‐up was observed among GT1 patients treated with OBV (17.8%) and GT3 patients (15.7%). The loss to follow‐up rate was significantly higher among individuals aged <60 years, those with a history of injection drug use (IDU), on opioid substitution therapy and with cirrhosis. Our findings indicate that loss to follow‐up exceeds viral failure in HCV DAA therapy and its rate varies significantly by genotype and treatment regimen. Depending on the aetiology of lost to follow‐up, personalized case management for those with medical complications and supporting services among IDU are needed to achieve the full benefits of effective treatments.